Por outros modos de bem viver: o pluriverso de alternativas e as ecovilas nas confluências comunitárias - Renata Amorim Almeida Fonseca; Marta de Azevedo Irving; Yasmin Xavier Guimarães Nasri; Graciella Faico Ferreira (e-cadernos ces)
In the face of global crises, various communities around the globe have been undertaking counter-hegemonic alternatives for social and productive organization. This essay takes up this premise, and through a narrative review of the academic literature and from a decolonial perspective, discusses the role of ecovillages within the pluriverse of alternatives, aiming to contribute to a critical reflection on the community confluence processes that strive to be both fair and ecological. It is understood that the socio-environmental practices of ecovillages, in confluence with the plurality of networked community alternatives, tend to represent a promising path for the necessary transition towards a fair and low-carbon society, in tune with the three-pronged dimensions of cultural identity, social equity and ecological sustainability associated with the communal ethics of Good Living.